Peran Pendidikan Agama Islam dalam Perkembangan Moral Anak Usia Dini - Akmalia, Fadhila Nur; Afifah, Annisa Nur; Zulfian, Zulfian; Ali, Moh. (Absorbent Mind, 2026)
This study aims to examine the role of Islamic Religious Education (IRE) in the moral development of early childhood and identify the methods used, as well as analyze the factors that influence its effectiveness. This research employs a qualitative library research method by collecting, analyzing, and synthesizing relevant literature sources, including books, scientific journals, and official documents related to IRE and early childhood moral development. The results indicate that IRE contributes significantly to children's moral formation through habituation (ta'widiyah), exemplary modeling (uswah hasanah), storytelling (qashash), and reward and punishment approaches. The integration of Islamic values in early childhood education programs has proven effective in instilling honesty, responsibility, empathy, and respect for others. The role of parents, teachers, and the surrounding environment is also decisive in supporting the success of IRE in shaping children's moral character. This study concludes that IRE is not merely religious instruction, but a holistic approach to character building aligned with early childhood education principles and national education goals in Indonesia.